2009
DOI: 10.1063/1.3141385
|View full text |Cite
|
Sign up to set email alerts
|

Observation of surface structure of 1-butyl-3-methylimidazolium hexafluorophosphate using high-resolution Rutherford backscattering spectroscopy

Abstract: The surface structure of 1-butyl-3-methylimidazolium hexafluorophosphate is studied by high-resolution Rutherford backscattering spectroscopy (HRBS) at room temperature. Elemental depth profiles are derived from the observed HRBS spectrum through spectrum simulation. While the obtained carbon profile has a sharp peak at the surface, the nitrogen profile shows a broader peak at a depth approximately 0.3 nm. These observations indicate that the butyl chain protrudes from the bulk liquid to the vacuum at the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
7
23
0
Order By: Relevance
“…In our previous papers, we have observed surface structures of various ILs. 27,36,37 We found that all observed ILs are shared almost equally between cations and anions although preferential orientations of either cation or anion were observed in some cases. Similar structures were also observed using various other techniques.…”
Section: -3mentioning
confidence: 74%
“…In our previous papers, we have observed surface structures of various ILs. 27,36,37 We found that all observed ILs are shared almost equally between cations and anions although preferential orientations of either cation or anion were observed in some cases. Similar structures were also observed using various other techniques.…”
Section: -3mentioning
confidence: 74%
“…Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum. 113 SFG measurements at the air-IL interface 118 showed that for longer alkyl chains, the number of gauche defects on this cation substituent decreased relative to short chains. This is in contrast to the substantial fraction of gauche defects on bulk alkylimidazolium cations in ILs deduced from Raman spectroscopy.…”
Section: Il Interfacesmentioning
confidence: 99%
“…A wide variety of experimental, theoretical, and simulation methods have been applied to the study of ILs at interfaces. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] Santos and Baldelli 112 have used interfacial sumfrequency generation ͑SFG͒ to show that at IL interfaces with gases or vacuum, alkyl chains on either the cations or the anions extend from the surface into the gas or vacuum. Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum.…”
Section: Il Interfacesmentioning
confidence: 99%
“…The direct recoil spectrometry measurements indicated a perpendicular distribution of imidazolium ring planes and a parallel orientation of butyl chains in [BMIM] cations in IL-gas interfacial region [94]. However, experimental characterizations based on sum frequency generation (SFG), high-resolution Rutherford backscattering spectroscopy and X-ray reflectivity observations [95][96][97][98] suggested that imidazolium rings prefer to take flat orientations along IL-gas interface, whilst butyl chains are loosely packed together and protruded from liquid phase into gas phase with a certain tilt. Additionally, in IL-solid interfacial region, nuclear magnetic resonance experiments showed that interfacial ionic structures of supported [BMIM][PF 6 ] IL depend strongly on solid surface types and the thickness of the confined IL film [93].…”
Section: Tetraalkylphosphonium-orthoborate Ionic Liquid-water Mixturesmentioning
confidence: 99%